1977
DOI: 10.1002/tera.1420150210
|View full text |Cite
|
Sign up to set email alerts
|

Spina bifida and so‐called asplenia syndrome occurring separately in sibs

Abstract: Attention is drawn to the possibility that neural-tube defects may sometimes be associted with the so-called asplenia syndrome (Ivemark syndrome). This hypothesis is based upon a family in which one child had spina bifida and hydrocephaly and another had cardiovascular and other fissural anomalies, similar to Ivemark syndrome. The family history, moreover, revealed several cases of anencephaly and/or spina bifida, both on the paternal and maternal sides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The asplenia anomaly is significantly more common in males than females [Van Mierop et al, 1972;Rose et al, 19751. In addition to the cardiovascular anomalies, which usually suggest the prognosis, there are frequently related extracardiac malformations such as bronchopulmonary, gastrointestinal, genitourinary, central nervous system, skeletal, and endocrine anomalies [Freedom, 1972;Van Mierop et al, 1972;Rose et al, 1975;Van Went et al, 1977;Mishalany et al, 19821.…”
Section: Introductionmentioning
confidence: 99%
“…The asplenia anomaly is significantly more common in males than females [Van Mierop et al, 1972;Rose et al, 19751. In addition to the cardiovascular anomalies, which usually suggest the prognosis, there are frequently related extracardiac malformations such as bronchopulmonary, gastrointestinal, genitourinary, central nervous system, skeletal, and endocrine anomalies [Freedom, 1972;Van Mierop et al, 1972;Rose et al, 1975;Van Went et al, 1977;Mishalany et al, 19821.…”
Section: Introductionmentioning
confidence: 99%
“…These studies differ from ours, however, because they included all neural tube defects rather than just open meningomyeloceles. 4,6 The incidence of congenital heart defects in our study was 37% of patients with an open meningomyelocele (considerably higher than the 1% risk given for the general population), with atrial septal defects being the most common abnormality. We also found that newborn girls with meningomyelocele are more frequently affected.…”
mentioning
confidence: 98%
“…Polysplenia was identified only in case 1, but the other cases also had heart and lung defects of the types found in lateralization disorders [Van Mierop et al, 1972]. Both Hirschsprung disease [Mishalany et al, 1982] and neural tube defects [Van Went et al, 1977] have been associated with lateralization disorders. Torra et al, [1996] reported an association between polysplenia and multicystic dysplastic kidneys.…”
Section: Discussionmentioning
confidence: 99%